Pentecost and Sinai: the Festival of Weeks as a celebration of the Sinai event - Pak, Se-jin (Library of Hebrew bible/Old Testament studies, 2008)
The Festival of Weeks in the Hebrew Bible and Second Temple Judaism -- Sinai traditions and the Festival of Weeks in the Hebrew Bible -- The Festival of Weeks and covenant renewal in Jubilees -- The Festival of Weeks and covenant renewal in the Dead Sea scrolls -- Pentecost and Sinai in Luke-Acts